PERKEMBANGAN DAN PERLINDUNGAN PENGETAHUAN TRADISIONAL DAN EKSPRESI BUDAYA TRADISIONAL DITINJAU DARI PERSPEKTIF HAK KEKAYAAN INTELEKTUAL - D. Hutabarat, Sylvana Murni (Jurnal Yuridis, 2015)
INTELLECTUAL PROPERTY, traditional knowledge and Traditional cultural expressions (TK & TCE) is a topic that until now haven't gotten the point .of the appointment. Indigenous peoples in this case as a custody often did not get his rights properly. The concept of ownership of communal customs make the mindset of those who are not commercial yet utilized by most developed countries. Indigenous people have not got the benefit sharing from their traditional wealth. The discussion at the international level have been held through WIPO and produce a special issue dealing with the institution of traditional knowledge and traditional cultural expressions in the international sphere, namely the Intergovernmental Committee on Intellectual Property and Genetic Resources, Traditional Knowledge and Folklore (JGC GRTKF). But until the last meeting still hadn't. Indonesia has had a draft regarding TK & TCE, however have still not been ratified. There is still much debate and correction of various parties. The procrastinators-nundaan this just makes the growing multitude of excessive exploitation of PT & EBT; from Indonesia by developed countries